Country Partnership Framework for Sri Lanka for the Period FY17-FY20 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2016)
The new Country Partnership Framework (CPF or framework) presents the engagement of the World Bank Group (WBG) in Sri Lanka over the next four years (fiscal years 2017-20 (FY17–20)). The CPF aims to support the achievement of some of the government’s medium-term goals in areas that are critical for reducing extreme poverty and promoting shared prosperity, and that are consistent with the WBG’s comparative advantage. Notably, the CPF provides the framework for engagement in several key policy areas. Following presidential and parliamentary elections in 2015, the new coalition government, the National Government of Consensus, has set out an ambitious vision for Sri Lanka. It focuses on supporting job creation in the private sector, advancing the country’s global integration, improving governance, enhancing human development and social inclusion, and balancing development with environmental conservation. The vision has been captured in the Prime Minister’s Economic Policy Statement of November 5, 2015. The new government’s development agenda is well aligned with the findings of the 2015 Systematic Country Diagnostic (SCD) for Sri Lanka. The SCD identified the most critical constraints and opportunities facing Sri Lanka in accelerating progress toward the twin goals of ending extreme poverty and promoting shared prosperity in a sustainable manner. The analysis concluded that key priorities are to address the country’s fiscal, competitiveness, and inclusion challenges, as well as cross-cutting governance and social, economic, and environmental sustainability challenges. The CPF is anchored in this analysis.